ANALISIS PELANGGARAN ETIKA PADA KASUS KORUPSI RAFAEL ALUN TRISAMBODO - Andi Nasywan Taghsya; Muhammad Nahdy Arrosyid; Rana Imran Shaukat (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This research explores the ethical and moral dimensions surrounding the corruption scandal involving the Minister of Agriculture in Indonesia. Even though it is a government institution responsible for public services, the government often fails to fulfill the principles of transparency, accountability and credibility. This case study focuses on the Minister's abuse of authority for personal gain, highlighting the need for deeper examination of ethical and moral violations in government practices. This research explores the motives and factors that contribute to corruption, recognizing the far-reaching consequences for both the state and the public's trust in government. Therefore, this research recommends implementing ethical values in governance to encourage a government that is free of corruption and has high morals.